ANALISIS TERJEMAHAN EUFEMISME ORGAN DAN AKTIFITAS SEKSUAL DALAM NOVEL FIFTY SHADES OF GREY - Desi Zauhana Arifin; Djatmika Djatmika; Tri Wiratno (Prasasti: Journal of Linguistics, 2017)
This research is aimed to: (1) identify the kinds of euphemism sexual organ and sexual activity in  Fifty Shades of Grey novel, (2) identify the translation techniques used by the translator in translating sexual organ and sexual activity with euphemism, (3) describe the impact  of translation technique which applied by the translator toward translation quality in terms of accuracy and acceptability.